Survival difference associated with controlled-release oxycodone analgesic therapy for oxaliplatin-induced peripheral neuropathy in advanced colorectal cancer patients. Issue 5 (2018) - Nagashima, Makoto; Hiranuma, Ayako; Oshiro, Takashi; Sato, Yu
No abstract available